Cuora mouhotii (Gray 1862) – Keeled Box Turtle - Das, Indraneil; McCormack, Timothy E.M.; Dijk, Peter Paul van; Hoang, Ha V.; Struijk, Richard P.J.H (Chelonian Research Foundation, 2016)
– The Keeled Box Turtle, Cuora mouhotii (Family Geoemydidae), is a small (carapace length up to ca. 250 mm), once poorly-known terrestrial species. Recent extensive research on the species in its natural habitat in northern Vietnam and Hainan, China, has significantly increased available knowledge of the species. Cuora mouhotii is a highly terrestrial turtle from the mesic forests of Southeast Asia. Two subspecies have been described, and intergradient populations are known. Relatively widespread, it is apparently abundant nowhere. Omnivorous, at least in captivity, the species is highly carnivorous in the wild but will also take fruit. Clutch size ranges from 1–9 eggs, with egg dimensions ca. 41 x 26 mm; incubation period in captivity varies from 82 to 120 days. Major threats to the species are loss of forest habitat from logging and commercial trade for Traditional Chinese Medicine and food. To a lesser extent capture for local consumption and both national and international pet trade are factors threatening this species.